Efisiensi Penggunaan Plat Cendawan Terhadap Plat KonvensionalPada Gedung Pascasarjana Ums - Agia, Vinca Rosea; , Dr. Mochamad Solikin; , Ir. H. Ali Asroni, MT (2016)
Redesign of Pascasarjana UMS Building by using flat slab aims to obtain the efficiency need of concrete material and steel reinforcement. The calculations was based on SNI-2847-2013 code and the material properties was remained (i.e.) f'c = 18,675 MPa, fyl = 400 MPa, and fyv = 240 MPa. The structure analyses were carried out using ETABS 2015, Microsoft Excel 2007, and AutoCAD 2016 was used to draw the detail results of redesign. The results are edge beam having dimension of 300x500 mm with longitudinal reinforcement of D12 and shear reinforcement of 2ϕ8-220. Column is redesign having dimension of 400x400 mm with longitudinal reinforcement of D16 and shear reinforcement of 2ϕ10-170. Flat slab is redesign having dimension of 150 mm and reinforcement of D10. Last, drop panel is redesign having dimension of 1500x1500x100 mm and reinforcement of D12. The volume of concrete after redesign is 109,17 m3 for the first floor. Comparing to volume of existing building of 154,05 m3, the redesign obtains efficiency value of 0,71. Meanwhile the volume after redesin of steel reinforcement is 5.187,80 kg for the first floor. Comparing the existing building of 27.666,64 kg, the redesign obtains efficiency value of 0,19.